Процесуальний статус поручителя у кримінальному провадженні: проблеми визначення та шляхи удосконалення - Фоміна, Т. Г.; Fomina, T. H.; Тетяна Фоміна (Проблеми законності. - 2018. - Вип. 142. - С. 200-210, 2018)
Досліджено процесуальний статус поручителя у кримінальному провадженні та сформульовано пропозиції до КПК України у частині регламентації порядку застосування особистої поруки. З цією метою у статті окремо розглянуто питання щодо порядку залучення поручителя, процесуальних вимог до нього. Запропоновано закріпити на рівні закону відповідний перелік прав таобов’язків поручителя. Исследован процессуальный статус поручителя в уголовном производстве и сформулированы предложения в УПК Украины в части регламентации порядка применения личного поручительства. С этой целью в статье отдельно рассмотрены вопросы о порядке привлечения поручителя,процессуальных требований к нему. Предлагается закрепить на уровне закона определенный перечень прав и обязанностей поручителя. The author has studied the procedural status of a pledger within criminal proceedings and has formulated propositions to the Criminal Procedural Code of Ukraine in part of regulating the procedure for the application of personal surety. For this purpose, the author of the article has separately studied the issue of the procedure for involving a pledger. It has been indicated that the initiative on involving a pledger for criminal proceedings may be initiated by both a suspect, accused, on whom the issue of the application of a preventive measure is being decided, and by persons who wish to take the bail of a suspect, accused. Instead, an investigating judge, court may choose a preventive measure in the form of a personal surety only if a pledger agrees or his application for taking a bail of a suspect, accused. It has been stressed that the statutory requirements are the trust or special confidence of an investigating judge, court to a pledger. Trust and special confidence, above all, are the awareness of an investigating judge, court that a pledger can contribute to the achievement of the purpose of a preventive measure and the execution of the duties by a suspect, accused, and secondly, they are based on the special moral qualities of a pledger, his authority. It has been concluded that personal surety is a preventive measure far from perfect in terms of legal enforcement, since the legislator has not resolved a number of important issues. Consequently, it is necessary to improve the provisions of the Art. 180 of the Criminal Procedural Code of Ukraine, and secondly, to regulate the procedural status of a pledger by amending the Criminal Procedural Code of Ukraine with a separate norm.
Procedural status of a pledger within criminal proceedings: problems of definition and the ways of improvement
Keywords: Україна; кримінальне провадження; запобіжні заходи; особиста порука; поручитель; права поручителя; обов’язки поручителя